SISTEM INFORMASI PERSEDIAAN BAHAN PRODUKSI BERBASIS WEB DENGAN MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT (STUDI KASUS PT. PACIFIC EASTREN COCONUT UTAMA) - Satria, Fahmi; Yudi Permana, Nana; Sidiq, Maulana (Jurnal Mahasiswa Sistem Informasi Galuh, 2025)
PT. Pacific Eastern Coconut Utama is the largest coconut processing company in Java Island, facing challenges in managing raw material inventory and production scheduling. The current system is still manual, using Microsoft Excel, which often causes delays in information flow, inaccurate stock records, and a high risk of human error. This research aims to design and develop an Integrated Web-Based Raw Material Inventory Information System using the Rapid Application Development (RAD) method. RAD was chosen for its ability to produce systems quickly through an iterative process that actively involves users at every development stage. The system includes stock management, recording incoming and outgoing goods, production scheduling, minimum stock detection, and automated report generation. Implementation uses PHP, MySQL, and XAMPP, with system modeling using UML. Testing was carried out with Blackbox and User Acceptance Testing, showing improvements in efficiency, real-time information access, and reduced recording errors.